2020
DOI: 10.1111/pcmr.12931
|View full text |Cite
|
Sign up to set email alerts
|

Rab GTPases: Key players in melanosome biogenesis, transport, and transfer

Abstract: Melanosomes are specialized intracellular organelles that produce and store melanin pigments in melanocytes, which are present in several mammalian tissues and organs, including the skin, hair, and eyes. Melanosomes form and mature stepwise (stages I–IV) in melanocytes and then are transported toward the plasma membrane along the cytoskeleton. They are subsequently transferred to neighboring keratinocytes by a largely unknown mechanism, and incorporated melanosomes are transported to the perinuclear region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 141 publications
1
27
0
Order By: Relevance
“…This is in agreement with studies in PD, describing that aSyn not only results in a loss of dopaminergic neurons [81] but also impairs the axonal transport of synaptic vesicles [79]. Mature melanosomes are transported from the perinuclear region to the periphery of melanocytes via the transport complex of RAB27A-melanophilin-myosin Va on the actin filament [21,82,83]. We, therefore, concentrated on the direct impact of aSyn on RAB27A but found no change after siSNCA treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with studies in PD, describing that aSyn not only results in a loss of dopaminergic neurons [81] but also impairs the axonal transport of synaptic vesicles [79]. Mature melanosomes are transported from the perinuclear region to the periphery of melanocytes via the transport complex of RAB27A-melanophilin-myosin Va on the actin filament [21,82,83]. We, therefore, concentrated on the direct impact of aSyn on RAB27A but found no change after siSNCA treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Mature melanosomes travel intracellularly along microtubule tracks and attach to the distal actin cytoskeleton via binding proteins including RAB27A (Ras-related protein RAB-27A). These transport complexes travel to the peripheral regions of the cell, the melanocytic dendrites, and accumulate at the distal tips [13,20,21]. The process of melanin secretion and uptake by the surrounding keratinocytes is still not well understood and discussed controversially [14,20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…As the results shown, dendritic number and length of B16F10 cells were increased because of DOI ( Figure 6 a–c) or TCB-2 ( Figure S6a–c ) treatment. The Western blot experiments revealed that the expression of proteins related to melanosome organization (GP100), melanosome transport (RAB7, RAB17, and RAB27), and melanocyte dendrites (RAC1 and CDC42) were increased in B16F10 cells with DOI ( Figure 6 d) or TCB-2 ( Figure S6d ) treatment [ 24 ]. Immunofluorescent staining of phalloidin showed an increase in cytoskeleton and dendrites with the DOI ( Figure 6 e) or TCB-2 ( Figure S6e ) treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, ULK1 knockdown in MNT-1 cells increased MITF expression, resulting in upregulation of melanogenesis (Figure 3a) [75]. Numerous proteins are involved in melanogenesis stage II, i.e., the melanosome biogenesis and maturation stage, including adaptor protein (AP)-1, AP-2, biogenesis of lysosome-related organelle complex (BLOC)-1, BLOC-2, BLOC-3, and various Rab GTPases [76][77][78][79][80]. UVRAG, identified as a beclin-1-binding autophagy-associated protein [81,82], has specialized functions in melanosome biosynthesis through its interaction with BLOC-1.…”
Section: Autophagy Machinery That Regulates Melanogenesismentioning
confidence: 99%